2021
DOI: 10.1021/acs.joc.1c02705
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Disulfide Formation by Thiol-Disulfide Interchange in SIT-Protected Cysteinyl Peptides

Abstract: Chemoselective disulfide formation is accomplished through a thiol-disulfide interchange approach using sec-isoamyl mercaptan (SIT) as an alkyl sulfenyl-protecting group of one of the Cys residues involved in the pairing. SIT has a dual and unique characteristic, acting as a masking group during the synthesis and directing disulfide formation in the presence of a free thiol. This novel approach is illustrated by the synthesis of several peptides of biological interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Furthermore, even though Trt was kept as a side-chain protecting group for Cys 14 , Cys 7 was protected with sec -isoamyl thiol (SIT), which has recently been developed by our groups . The SIT group is totally stable for the synthesis (elongation and global deprotection) and participates in a chemoselective disulfide formation by the thiol-disulfide interchange, in our case, with the free thiol after global deprotection of the Cys 14 . The SIT-protected peptide showed a much better purity by HPLC (70%) and LCMS (Figures and S29) compared to the first synthetic attempt.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, even though Trt was kept as a side-chain protecting group for Cys 14 , Cys 7 was protected with sec -isoamyl thiol (SIT), which has recently been developed by our groups . The SIT group is totally stable for the synthesis (elongation and global deprotection) and participates in a chemoselective disulfide formation by the thiol-disulfide interchange, in our case, with the free thiol after global deprotection of the Cys 14 . The SIT-protected peptide showed a much better purity by HPLC (70%) and LCMS (Figures and S29) compared to the first synthetic attempt.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of heterodetic disulfide peptides, an additional benefit is that oxidation (cyclization) in solution usually requires a very high dilution because it is a thermodynamic process, while on-resin cyclization is carried out with the concourse of only a little amount of solvent. Our group recently developed sec -isoamyl mercaptan (SIT) for the protection of the thiol of Cys. , This protecting group, with less steric hindrance than S t Bu, can be better removed by mild reducing agents such as 1,4-dithiothreitol (DTT), which in many cases does not remove the S t Bu . It was later demonstrated that the SIT protecting group for the side chain of Cys allows for chemoselective disulfide formation in peptides through a thiol–disulfide interchange method.…”
Section: Resultsmentioning
confidence: 99%
“…Our group recently developed sec-isoamyl mercaptan (SIT) for the protection of the thiol of Cys. 45,46 This protecting group, with less steric hindrance than StBu, can be better removed by mild reducing agents such as 1,4-dithiothreitol (DTT), which in many cases does not remove the StBu. 45 It was later demonstrated that the SIT protecting group for the side chain of Cys allows for chemoselective disulfide formation in peptides through a thiol−disulfide interchange method.…”
Section: Or Chlorotrityl-(ct) Resins]mentioning
confidence: 99%
“…14 Although the primary purpose of SIT was to serve as an alternative to the -StBu group, further studies demonstrated that the presence of this protecting group on the peptide after cleavage acted to direct disulfide bond formation in the presence of a free thiol. 15 Thus, to apply this methodology, the linear precursor H-C(SIT)KWKLFKKIGAVLKVLC-NH 2 was synthesized using SIT for protection of the Cys 1 residue and a trityl (Trt) protecting group for the Cys 17 . After cleavage and precipitation, the crude peptide, whose integrity was confirmed by MS (Figure S12), was dissolved in a 0.05 M NaHCO 3 solution to a dilution of 0.1 mM at a pH of approximately 8 (Figure 2A).…”
Section: T H Imentioning
confidence: 99%
“…Our group recently developed a novel disulfide-based protecting group named sec -isoamyl­mecaptan (SIT) for the Cys side chain . Although the primary purpose of SIT was to serve as an alternative to the -StBu group, further studies demonstrated that the presence of this protecting group on the peptide after cleavage acted to direct disulfide bond formation in the presence of a free thiol . Thus, to apply this methodology, the linear precursor H-C­(SIT)­KWKLFKKI­GAVLKVLC-NH 2 was synthesized using SIT for protection of the Cys 1 residue and a trityl (Trt) protecting group for the Cys 17 .…”
mentioning
confidence: 99%